2005
DOI: 10.1073/pnas.0504929102
|View full text |Cite
|
Sign up to set email alerts
|

Ground-based and remotely sensed nutrient availability across a tropical landscape

Abstract: Tropical soils often are assumed to be highly weathered and thus nutrient-depleted, but this prediction applies primarily to geomorphically stable surfaces. Topography complicates the assumption of nutrient depletion, because erosion can enhance the supply of nutrients to tropical ecosystems. Consequently, understanding nutrient availability across landscapes requires a spatially explicit assessment of the relative strength of depletion and enhancement. We document the relationship between foliar nutrients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 28 publications
6
69
1
2
Order By: Relevance
“…While the results of erosion rate on foliar chemistry have been explored both on the ground [23] and from aircraft [24], this is the first effort that uses LiDAR to detect the effects of erosion rate on forest structure in a tropical forest. Thus, this work indicates another mechanism by which differences across elevation lead to differences in forest structure and function, one of the longest standing observations in ecosystem science and biogeography [25].…”
Section: General Importancementioning
confidence: 99%
“…While the results of erosion rate on foliar chemistry have been explored both on the ground [23] and from aircraft [24], this is the first effort that uses LiDAR to detect the effects of erosion rate on forest structure in a tropical forest. Thus, this work indicates another mechanism by which differences across elevation lead to differences in forest structure and function, one of the longest standing observations in ecosystem science and biogeography [25].…”
Section: General Importancementioning
confidence: 99%
“…P, K, Mg and Ca concentrations have been examined in savannah grasses [27] as well as for willow, olive, grass and heather foliage [28]. At airborne scales, AVIRIS data were used to estimate area-integrated P concentrations in tropical forests of Hawaii [29] and African savannah using HyMap data [30]. Mirik et al [31] found a statistically significant relationship between a simple ratio vegetation reflectivity index (1129 nm/469 nm) and P concentration on an area basis in the forage vegetation of Yellowstone National Park using PROBE-1 data.…”
Section: Introductionmentioning
confidence: 99%
“…Over time, atmospheric nitrogen is added to soils by fixation or wet /dry deposition, which is why older Hawaiian soils (Kohala) tend to have more nitrogen than younger Hawaiian soils (Mauna Kea) ( Vitousek et al 2003, Vitousek 2004, Porder et al 2005. By this logic one would expect Mauna Loa streams to have lower nitrate c oncentrations than Mauna Kea streams.…”
Section: Discussionmentioning
confidence: 99%